Impact of Probiotic and Bioprotective Cultures on the Quality and Shelf Life of Butter and Buttermilk - Carlos Pereira; David Gomes; Susana Dias; Sandra Santos; Arona Pires; Jorge Viegas (Dairy)
In this study, butter and the corresponding buttermilk samples were produced with cream fermented by aromatic (A) or probiotic (P) cultures with or without complementary bioprotective culture (BC). The samples were characterised for their composition and colour parameters. Texture and rheological properties were evaluated at 10 and 20 °C. Microbiological (lactobacilli, lactococci, and yeast and mould counts) and sensory (aroma, taste, texture, and global evaluation) analyses were also performed. All butter sample characteristics were in accordance with the Portuguese standard. Regarding colour, the sample obtained with cream fermented by probiotics plus bioprotective culture (PBC) presented higher L* and b* values, indicating a slightly higher yellow chroma. However, colour differences (ΔEab*) in the butter samples were, in most cases, not detectable by a common observer. Butter samples P and PBC presented a significantly higher viscous modulus and consequently higher dynamic viscosity values (ca. log 6.5 Pa.s at 10 °C and log 5 Pa.s at 20 °C). Butter samples presented a pseudoplastic behaviour, and rheological parameters showed a high dependence on temperature. The counts of lactobacilli and lactococci in the butter samples were of the order of log 7–8 CFU/g, while yeast and mould counts were lower than log 2 CFU/g until the 30th day of storage, after which they showed a sharp increase to ca. log 5 CFU/g between the 30th and the 60th days of storage. Regarding sensory attributes of butter, sample P received the highest overall liking, followed by samples ABC and PBC. Sample A was the least appreciated. Buttermilk samples presented significant differences regarding their composition, viscosity, and colour parameters. In all cases, lactobacilli and lactococci counts exceeded log 7 CFU/mL after 30 days of storage, but yeast and mould counts were of the order of log 5–6 CFU/mL at the 15th day of storage. Samples P and PBC presented yeast and mould counts ca. 1–2 log cycles lower than samples A and ABC, indicating the potential of probiotic and bioprotective cultures to extend the shelf life of the product. Regarding the sensory attributes of buttermilk, samples P and PBC received the highest overall liking, followed by sample ABC. Sample A received the lowest scores, as had occurred with the butter samples. However, in all cases, the scores obtained by the buttermilk samples were lower compared to the ones of the corresponding butter. It can be concluded that both probiotic butter and buttermilk present high levels of lactobacilli and lactococci and can maintain their probiotic potential throughout the storage period.